Modelling and analysing an innovative cooperation to support operation of a science centre - Darnai , Balázs; Gályász, József (Applied Studies in Agribusiness and Commerce, 2015)
A science centre was built in Debrecen with the purpose to extend natural scientific knowledge and increase commitment to science and innovation in an experience-focused way. In addition to science centres’ original role of education and scientific communication, their function has been extended for today with showcasing innovation and innovation findings, thereby “grabbing their slice” of the regional innovation process. However, in order to succeed, it is indispensable to maintain these institutions in the long run and to constantly renew their innovation content. By integrating the process established with using the “Triple Helix” approach, it is possible to assure one of the most important principles of the institution in the long run, which is its constant renewal that provides a wide range of the society with experiencebased “tangible” knowledge. By following the concept we use, it became obvious that a science centre – as an organisation which creates knowledge – calls for the direct collaboration of the government, science and business actors in order to successfully operate in the long run, to attain its goals and, consequently, to develop the innovation potential of the region. However, the accumulated knowledge as a result of strategic partnerships can only contribute to establishing regional knowledge if the user – the organisation of the Science centre in Debrecen – is able to convey it successfully to the members of the fourth and fifth helix. JEL code: R11